The Impact of the Two Dispute Resolution Processes in Negotiations - Subbarao, A. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This paper attemps to answer the questions as to why the federal public servants alther their options from the arbitration process to the conciliation process.